2018
DOI: 10.1155/2018/8093719
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Damping Characteristics of Lightweight Clay‐EPS Soil under Cyclic Loading

Abstract: Lightweight Clay-EPS Soil (LCES) is a newly developed material which has many merits such as the adjustability of strength and density, simplicity for construction, and economical efficiency. It has been widely applied in practical engineering, e.g., soft ground improvement, the solvent of bridge head jump, earthfill of pipeline, and broadening of highway. Meanwhile, construction castoff and industrial waste can be recycled as a major ingredient in LCES. The dynamic deformation characteristics of LCES and clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, under the load level of 0.8, the specimens of FC7 and FC9 failed after approximately 1200 and 500 cycles, respectively, following a rapid increase of axial strain. De Andrade et al [ 44 ] and Zhou et al [ 45 ] obtained similar findings in that the lightweight cement composites did not fatigue up to 10 6 cycles when the applied stress was less than 50% of the peak stress, whereas they could fail below 10 3 cycles beyond that load level. The studies conducted by Gao et al [ 46 ] and Khajeh et al [ 21 ] also indicated that failure of geo-foam materials was observed after the number of cycles exceeds 10 3 and is less than 10 4 .…”
Section: Resultsmentioning
confidence: 67%
“…However, under the load level of 0.8, the specimens of FC7 and FC9 failed after approximately 1200 and 500 cycles, respectively, following a rapid increase of axial strain. De Andrade et al [ 44 ] and Zhou et al [ 45 ] obtained similar findings in that the lightweight cement composites did not fatigue up to 10 6 cycles when the applied stress was less than 50% of the peak stress, whereas they could fail below 10 3 cycles beyond that load level. The studies conducted by Gao et al [ 46 ] and Khajeh et al [ 21 ] also indicated that failure of geo-foam materials was observed after the number of cycles exceeds 10 3 and is less than 10 4 .…”
Section: Resultsmentioning
confidence: 67%
“…The strength of the structural EPS concrete specimens prepared in this study fulfilled the strength level of C30, and the dynamic elastic modulus was a magnitude order less than that of plain concrete of the same strength level. It was reported that the higher the dynamic elastic modulus of concrete was, the greater brittleness and worse crack resistance of concrete would be [12]. Thus, it could be seen that the structural EPS concrete had stronger toughness and superior fatigue stability.…”
Section: Resultsmentioning
confidence: 99%
“…Researches on the dynamic properties of EPS concrete were mainly focused on dynamic compressive/tensile performance [10,11] and energy absorption properties under drastic instantaneous impact [4,5]. Actually, EPS concrete could be designed to endure cyclic loadings, such as traffic loads, and its dynamic properties would not be the same as those measured in other conditions [12]. Hence, it is important to study the dynamic properties of EPS concrete under cyclic loadings.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the stress-strain characteristics of EPS lightweight mixed soil (RDSEM) under cyclic loading, Zhou et al [32] evaluated the effects of cement, EPS particles, and confining pressure (σ 3 ) through a dynamic triaxial test. Zhou et al [33] studied the effects of different cement contents, EC, and σ 3 on the dynamic elastic modulus (E d ) and damping ratio (λ) of EPS granular lightweight clay (LCES) through a dynamic triaxial test, and compared them with the dynamic characteristics of clay. Gao et al [34] studied the changes of stiffness and damping ratio of EPS lightweight soil with EPS, cement content, and confining pressure under low strain.…”
Section: Introductionmentioning
confidence: 99%